The Role of Counsellors in Empowering Dairy Farmers in the Southern Bandung Livestock Cooperative (A Case Study on Dairy Farmer Groups in TPK Cipanas, Margamukti Village, Pangalengan District, Bandung Regency) - Rizky Ayuna Budiman; Marina Sulistyati; Syahirul Alim (Green Publisher Indonesia, 2024)
The purpose of this research is to determine the role of extension workers, the empowerment of dairy farmers, and the relationship between the role of extension workers and the empowerment of dairy farmers in TPK Cipanas. The research was conducted in December at TPK Cipanas, Margamukti Village, Pangalengan District, Bandung Regency. The research method involved a survey of 40 respondents using proportional random sampling. The data obtained were analyzed using Spearman's Rank Correlation. The research results indicated that 1) the role of extension workers was in the moderate category (38.4%) and 2) the empowerment of farmers was in the moderate category (34.8%). Furthermore, there was a positive and moderately strong relationship between the role of extension workers and the empowerment of farmers with a Spearman's Rank Correlation value (???????? = 0.607).